Restoring Function and Aesthetics in a Class II Division 1 Patient with Amelogenesis Imperfecta: A Clinical Report - Doruk, Cenk; Ozturk, Firat; Sari, Fatih; Turgut, Mehmet (European Journal of Dentistry, 2011)
Amelogenesis imperfecta (AI) encompasses a complicated group of hereditary conditions that cause developmental alterations in the structure of the enamel in the absence of a systemic disorder. AI primarily affects the quality and/or quantity of dental enamel, and it may affect all or only some of the teeth in the primary and/or permanent dentition. This clinical report describes the oral rehabilitation of a 21-year-old man diagnosed with hypomaturation-type AI. He presented with discolored and mutilated teeth. Cephalometrically, the patient has skeletal class II malocclusion due to mandibular deficiency considered as a result of maxillary constriction. The interdisciplinary approach was followed because of the complex needs of the patient. The aim of treatment was to restore aesthetics, improve malocclusion and masticatory function. Aesthetic and functional expectations were met with metal ceramic restorations. In this report, the interdisciplinary approach for a patient with AI and a malocclusion is described. (Eur J Dent 2011;5:220-228)
Keywords: Amelogenesis imperfect; Interdisciplinary study; Orthodontic appliance